A Review on Oil Sardine III. Oil and Meal Industry - Madhavan, P.; Nair, T. S. Unninkrishnan; Balachandran, K. K. (Fishery Technology, 1974)
Sardine oil industry started to gain prominence in the early 20th century. It has remained an age-old practice of fishermen to use sardine oil for painting the bottom of their fishing crafts . Conversion of sardine oil into factice, a filler in rubber compounding industry; use as a vehicle in surface coating material and as printing ink base, as an additive in lubricating oil etc. are also other areas where it finds an application. During glut seasons whole fish as such were used as manure. Solvent extraction of the odor-bearing compounds and residual fat from the sardine press-cake prepared under sanitary conditions can result in a more concentrated light coloured flour containing more than 80% protein of almost blunt taste.